To Stitch and to Teach: A critical reflection on pedagogy as embodied praxis - Perold-Bull, Karolien (Critical Studies in Teaching and Learning, 2025)
The late Professor Elmarie Costandius contributed to stitching me together as creative practitioner in the field of South African higher education. In her memory, this paper reflects on the practicalities involved in pedagogy as embodied praxis through an autoethnographic lens. I have read memories of our pedagogical interactions through Tim Ingold’s theories of embodied making. Ingold believes that making is not a process of imposing preconceived form on the material world but rather involves processes that allow meaningful form to emerge through active engagement with the world’s materiality. The result of this autoethnographic enquiry is presented as a patterned memoir; a practical example of stitching together a pedagogical praxis built on the premise of process, trans-disciplinarity, and affecting tangible, real-life change. The purpose of the memoir is to make Elmarie’s pedagogical praxis accessible to other educators, thus facilitating her legacy in shaping future education, specifically locally, in productive, tangible ways.